Growth and body composition of Peruvian infants in a periurban setting - Iannotti, Lora L.; Zavaleta, Nelly; Leon, Zulema; Caulfield, Laura E. (SAGE Publications, 2009)
Previous growth studies of Peruvian children have featured high stunting rates and limited information about body composition.We aimed to characterize anthropometric measures of Peruvian infants 0 to 12 months of age in relation to the international growth references and biological, environmental, and socioeconomic factors.Infants ( n = 232) were followed longitudinally from birth through 12 months of age from a prenatal zinc supplementation trial conducted in Lima, Peru, between 1995 and 1997. Anthropometric measures of growth and body composition were obtained at enrollment from mothers and monthly through 1 year of age from infants. Weekly morbidity and dietary intake surveillance was carried out during the second half of infancy.The prevalence rates of stunting, underweight, and wasting did not exceed 4% based on the World Health Organization growth references. Infants of mothers from high-altitude regions had larger chest circumference ( p = .006) and greater length ( p = .06) by 12 months. Significant predictors of growth and body composition throughout infancy were age, sex, anthropometric measurements at birth, breastfeeding, maternal anthropometric measurements, primiparity, prevalence of diarrhea among children, and the altitude of the region of maternal origin. No associations were found for maternal education, asset ownership, or sanitation and hygiene factors.Peruvian infants in this urban setting had lower rates of stunting than expected. Proximal and familial conditions influenced growth throughout infancy.